Talimogene laherparepvec upregulates immune-cell populations in non-injected lesions: findings from a phase II, multicenter, open-label study in patients with stage IIIB–IVM1c melanoma. Issue 3 (30th March 2021) - Malvehy, Josep; Samoylenko, Igor; Schadendorf, Dirk; Gutzmer, Ralf; Grob, Jean-Jacques; Sacco, Joseph J; Gorski, Kevin S; Anderson, Abraham; Pickett, Cheryl A; Liu, Kate; Gogas, Helen
Abstract : Background: Talimogene laherparepvec (T-VEC), an oncolytic virus, was designed to selectively replicate in and lyse tumor cells, releasing tumor-derived antigen to stimulate a tumor-specific immune response. Methods: In this phase II study in patients with unresectable stage IIIB–IV melanoma, we evaluated non-injected lesions to establish whether baseline or change in intratumoral CD8 + T-cell density (determined using immunohistochemistry) correlated with T-VEC clinical response. Results: Of 112 enrolled patients, 111 received ≥1 dose of T-VEC. After a median follow-up of 108.0 weeks, objective/complete response rates were 28%/14% in the overall population and 32%/18% in patients with stage IIIB–IVM1a disease. No unexpected toxicity occurred. Baseline and week 6 change from baseline CD8 + T-cell density results were available for 91 and 65 patients, respectively. Neither baseline nor change in CD8 + T-cell density correlated with objective response rate, changes in tumor burden, duration of response or durable response rate. However, a 2.4-fold median increase in CD8 + T-cell density in non-injected lesions from baseline to week 6 was observed. In exploratory analyses, multiparameter immunofluorescence showed that after treatment there was an increase in the proportion of infiltrating CD8 + T-cells expressing granzyme B and checkpoint markers (programmed death-1, programmed death-ligand 1 (PD-L1) and cytotoxic T-lymphocyte antigen-4) in non-injected lesions, together with an increase in helper T-cells. Consistent with T-cell infiltrate, we observed an increase in the adaptive resistance marker PD-L1 in non-injected lesions. Conclusions: This study indicates that T-VEC induces systemic immune activity and alters the tumor microenvironment in a way that will likely enhance the effects of other immunotherapy agents in combination therapy. Trial registration number: NCT02366195 .